The Symbol Digit Modalities Test:: Normative Data from a Large Nationally Representative Sample of Australians - Watson, N; Wooden, M; Kiely, K; Butterworth, P (My University, 2014)
Data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey were used to calculate weighted norms for the written version of the Symbol Digits Modalities Test (SDMT) by gender, 5-year age groups and four levels of educational attainment. The sample comprised 14,456 Australians (47% male; age range 15–100), of whom 25% reported a tertiary qualification, 30% reported a technical qualification (diploma or trade certificate), 16% reported completing Year 12 (final year of high school), and 29% reported their highest level of educational attainment to be Year 11 or below. Participants were excluded if they reported physical or neurological conditions that limited performance. Age, gender, and education were all significantly associated with SDMT performance, as was poor health, and cultural background. The reported norms are of greater scope and precision than previously available and have utility in a range of clinical and research settings. Indeed, normative data for the SDMT that are representative of a national population have not previously been published.
Archives of Clinical Neuropsychology
Keywords: Surveys and Survey Methodology; Ageing; Surveys and Survey Methodology; Ageing; Surveys and Survey Methodology; Ageing; Ageing